1G.005 Drug-related disorder diagnoses and demographic characteristics associated with legal intervention-related injuries. (14th March 2021) - Bunn, Terry; Bush, Ashley; Ward, Patrick; Liford, Madison
Abstract : Background: Law enforcement official (LEO) use of force during suspect restraint/apprehension is a serious concern resulting in suspect and LEO injuries. Drug use has been identified as a factor in use-of-force incidents. Methods: This study characterized Kentucky LEO and suspect legal intervention (LI) related injuries and assessed associations between substance use disorder (SUD) diagnoses and demographic characteristics with ICD-10-CM coded LI emergency department (ED) injury visits for years 2016–2018. Logistic regression models examined the most common LEO and suspect injuries. Results: There was a larger proportion of LEO LI hand injury ED visits compared to suspects; there was a larger proportion of suspect LI head injury ED visits compared to LEOs. Among suspect LI ED visits, there were higher odds of head injury ED visits with a SUD (adjusted OR = 1.92), Appalachian county residence (adjusted OR = 1.45), or manhandling LI (adjusted OR = 1.42). No association was found between SUD diagnoses or demographic characteristics and LEO legal intervention hand-related injury ED visits. Conclusions: When de-escalation techniques fail and LI is required, LEO tactics other than use-of-force are recommended to reduce injuries. Crisis Intervention Team and other trainings may prove beneficial by reducing the need for force; in cases involving SUDs, it is recommended that suspects be referred to treatment. Learning Outcomes: LEOs should employ alternative tactics to reduce officer and suspect use-of-force injuries during LI. Safer options include control techniques, striking zones on suspects, and other tools and body parts when LEO de-escalation training techniques have failed.